Interview with Chilean Activist Victor Toro - Clyde Lanford Smith (Social Medicine, 2008)
Victor Toro Ramirez. Immigrant activist in the United States, ex-political prisoner of the military dictatorship in Chile and in process of deportation by the Bush government and its immigration scandal.